Analysis of Medical Equipment Control Through Handover Tools in the Inpatient Ward of Hospital - Tatik Wahyuni; Tuti Afriani; Kuntarti Kuntarti; Rr Tutik Sri Hariyati; Eka Pujiyanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Medical equipment control is a crucial aspect in supporting the continuity and effectiveness of nursing services in inpatient wards. This study aimed to evaluate internal and external factors influencing the effectiveness of medical equipment control and to formulate the need for developing a structured, documentation-based handover tool. This preliminary study was conducted in hospital inpatient wards involving Nurse Unit Managers (NUMs) and staff nurses. Data were collected through in-depth interviews, field observations, and questionnaires. Medical equipment control processes were examined using the POSAC management framework. Questionnaire data were analyzed descriptively, while overall data were analyzed using POSAC and SWOT analyses, followed by IFE and EFE matrices to formulate improvement strategies. Data validity was ensured through source and method triangulation. The findings indicated that medical equipment control had not been optimally implemented due to the absence of standard operating procedures, inconsistent documentation, unequal distribution of equipment, and the lack of routine evaluation. Analysis of external factors revealed significant opportunities, including government regulations, accreditation requirements, technological advances, and increasing public expectations for fast and accurate services. A standardized, user-friendly, and integrated medical equipment handover system is required to improve efficiency, accuracy, and the overall quality of nursing services.